The Influence of Modernization and the Economy in Shaping Social Change in Urban and Rural Societies: A Sociological Review of Health - Rusmana, Asep (Ann Publisher, 2025)
Background. Modernization and economic dynamics are the main factors driving social change in urban and rural communities. These changes not only affect social and cultural structures but also significantly impact public health patterns, access to health services, and healthy living behaviors. Purpose. This article aims to analyze the influence of modernization and economics on social changes that affect public health in urban and rural areas. Method. The method used is a literature review with a qualitative-descriptive approach, drawing on scientific literature, policy reports, and previous research results. Conclusion. The results show that modernization accelerates the transformation of lifestyles, value systems, and health consumption patterns, while economic factors determine the level of accessibility and quality of health services. In urban communities, modernization tends to increase access to health facilities but also triggers the development of degenerative diseases due to lifestyle changes. In contrast, in rural areas, economic and infrastructure constraints lead to health inequalities, although social solidarity is still relatively strong. Implementation. This article emphasizes the importance of the health sociology approach in formulating equitable and health-oriented development policies.